Research on the Application of VR Technology in the Field of Automotive Marketing - Lu, Jin; Ren, Lulu; Guo, Xin (International Journal of Global Economics and Management, 2024)
With the increasingly fierce competition in the automotive market, the application of VR technology in automotive marketing by automotive enterprises plays an important role in improving consumer experience, gaining competitive advantages in the industry, and boosting the digital transformation of automotive enterprises. This paper reviews the current situation of VR technology in the field of automobile marketing, studies relevant policies, summarizes the application of VR technology in automobile marketing, and finally forecasts the development trend of VR technology in automobile marketing and gives relevant suggestions. The purpose of this paper is to provide some reference for promoting Chinese automobile enterprises to obtain competitive advantage in global automobile marketing.